Peningkatan Kualitas Layanan Wisata Melalui Pelatihan Delivering Happiness Bagi Karyawan Dago Dream Park - Meily Margaretha; Sherlywati Sherlywati; Susanti Saragih; Imelda Junita; Fanny Kristine; Yolla Margaretha; Kezia Kurniawati Nursalin; Jahja Hamdani (SWARNA: Jurnal Pengabdian Kepada Masyarakat, 2026)
This article describes a community service program that used Delivering Happiness as the main framework for strengthening the service capability of Dago Dream Park employees in Bandung. The program was developed from the practical assumption that service quality in tourism is shaped not only by technical procedures, but also by employees’ emotional climate, shared values, and sense of contribution. The activity was carried out on 29 April 2026 with 55 participants using a participatory training model that combined a brief needs review, pre-test, four learning sessions, reflective worksheets, group discussion, post-test, and individual action planning. The material focused on workplace happiness, WOW service, organizational culture, and meaningful work, then was contextualized to the interaction patterns commonly found in tourism services. The main outputs of the program were a training module, a Happiness Thermometer worksheet, a Culture Check sheet, pre-test and post-test instruments, and written personal commitments for workplace improvement. After the activity, participants showed better conceptual understanding, indicated by the change in the average score from 60% to 95%, and qualitatively demonstrated stronger awareness of caring service behaviour. This program indicates that a human-centered training design can be used as a practical strategy to improve service experience in tourism destinations.